Podcasting as an Alternative Method of Social Research - Rocky Prasetyo Jati (2022)
This study examines the use of podcasting as a method in social research. The development of information and communication technology allows the use of various media in the research process. This article introduces podcasting as part of the method and not just as a research subject. Through strategies commonly used in qualitative approaches, such as ethnography, phenomenology, or case studies, podcasts can be used as innovative tools to support researchers in finding research answers and presenting research results. This article uses an example of implementing a Ã¢â‚¬Å“rock castÃ¢â‚¬Â podcast to illustrate this method's potential and implementation stages. Thus, this article argues that podcasts can be considered as an alternative method for social research.